Microplastic- An Imposing Commination to the Aquatic Ecosystem and its Removal Strategies in Wastewater Treatment Plants: A Systematic Review - Modak, Anirudh; Basu, Shamayita (Journal of Sustainability and Environmental Management, 2022)
Plastic is broadly used for various human interests (technological devices, food packaging, medical products, etc.) and there is an increasing concern about the risks for our surrounding environment and health. In particular, microplastics (MPs), both primary and secondary, occur in all environmental pockets and constitute a potential warning, since they easily enter into the food chain. Moreover, microplastics have the ability to absorb diverse pollutants, which thereby get accumulated inside human body via processes of bioaccumulation and biomagnification. A systematic review was conducted to determine the effectiveness of wastewater treatment facilities (WWTPs) in removing microplastics. Published research on the effectiveness of wastewater treatment plants (WWTPs) for microplastic removal were searched using international databases (PubMed, Science Direct, and Scopus). Contamination of MPs in aquatic environment has presently been recorded as a transpiring environmental threat because of their fatalistic impact on the ecosystem. Their sources are numerous, but, undoubtedly, all are from synthetic matters. The sources of MPs are cosmetics and products of personal care, textile and tyre, abrasion processes of some other plastic products, bitumen and paints for road marking. Due to their low density and tiny particle size, MPs get easily extravasated into the wastewater drainage systems. Therefore, the municipal wastewater treatment plants (WWTPs) are designated to be the foremost recipients of MPs prior to getting excreted into the natural water reservoirs. The focus of this article is to put forward an all-inclusive review in order to preferably understand the channels of MPs into the environment, their characteristics in wastewater, and most importantly, the removal efficiency of MPs of the subsisting wastewater treatment technologies, as arrogated by the WWTPs. This review also encompasses the expansion of budding microplastics treatment technologies that have been investigated till date. Then, in the not-too-distant future, effective and standardised techniques for measuring MPs should be developed, as well as a greater understanding of sources and strategies for reducing microplastics contamination of treated effluent.